Assignment of absolute stereostructures through quantum mechanics electronic and vibrational circular dichroism calculations. Issue 1 (2nd January 2016) - Dai, Peng; Jiang, Nan; Tan, Ren-Xiang
Abstract: Elucidation of absolute configuration of chiral molecules including structurally complex natural products remains a challenging problem in organic chemistry. A reliable method for assigning the absolute stereostructure is to combine the experimental circular dichroism (CD) techniques such as electronic and vibrational CD (ECD and VCD), with quantum mechanics (QM) ECD and VCD calculations. The traditional QM methods as well as their continuing developments make them more applicable with accuracy. Taking some chiral natural products with diverse conformations as examples, this review describes the basic concepts and new developments of QM approaches for ECD and VCD calculations in solution and solid states.